Receptor modelling of airborne pollutants along major highways in lagos, southwest, Nigeria - Ayodele P. Olufemi; Oladimeji A. Babatunde; Adebiyi S. Adebayo; Oghenenyovwe Ovie; Adekunle B. Toyeje; Opeyemi R. Omokungbe; Pelumi. O. Abiodun (Discover Applied Sciences)
Abstract Modeling techniques that can forecast air pollution concentrations under a range of weather and traffic scenarios are essential for managing local air quality. Four low-cost air monitoring devices were deployed to locations proximate to major highways for the measurements of atmospheric pollutants (gaseous and particulate matter). The objectives are to measure the concentration of the pollutant, apportion local sources of ambient air pollutants, and investigate distant sources of pollutants impacting all sampling locations using the Sensor Network for Air Quality (SNAQ), Positive Matrix Factorization (PMF) and Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) respectively. The average concentrations with standard deviation of the air pollutants varied from 1100.76 ± 743.64 to 2316.76 ± 1309.45 ppb, 17.17 ± 12.05 to 83.11 ± 51.87 ppb, 58.94 ± 30.54 to 97.09 ± 33.14 ppb, 63.83 ± 28.85 to 78.64 ± 30.99 ppb, 64.39 ± 60.87 to 101.18 ± 73.86 $$\:μ\:g/{m}^{3}$$ , and 282.39 ± 312.22 to 101.18 ± 73.86 $$\:μ\:g/{m}^{3}$$ for CO, NO, NO2, O3, PM2.5, and PM10 respectively. The measured average value of the pollutants exceeded the recommended threshold by World Health Organization (WHO) which signifies elevated level of pollutants in the ambient air. Duncan Multiple Range Test (DMRT) result showed substantial statistical variation in the concentration of the pollutants across the sampling sites, indicating emission from other local sources that is peculiar to each sampling sites. The PMF model revealed vehicle emission as the main source of pollution with highest percentage contribution of 38.6% closely followed by dust re-suspension/windblown with 32.7% percentage contribution to ambient pollution levels throughout the sample sites. HYSPLIT result showed that the surface was predominantly impacted by air masses originating from off the coast of Atlantic Ocean and transported inland across the Gulf of Guinea and the mid boundary layer was influenced by transport from the Sahara Desert.